Rancang Bangun Website Sistem Pengembangan Usaha Mikro dan Kecil Pada Kedai Nyoklat Klasik Delisya Delicious - Pranatawijaya, Viktor Handrianus; Christie, Sagita Amaria (Universitas Palangka Raya, 2022)
Kedai Nyoklat Classic Delisya Delicious is one of the business units engaged in beverages and snacks in the city of Palangka Raya. Based on the observations I made of this shop, at this time Kedai Nyoklat is experiencing difficulties in conveying information, because Kedai Nyoklat only uses Instagram social media to promote and is still not consistent in delivering information. Therefore,